2020
DOI: 10.1111/and.13751
|View full text |Cite
|
Sign up to set email alerts
|

Centella asiaticaalleviates diabetes‐induced changes in fatty acid profile and oxidative damage in rat testis

Abstract: The in vivo effects of Centella asiatica L. Urban (Family: Apiaceae; CA) on diabetesinduced testicular fatty acid misdistribution and oxidative injury were investigated. Diabetic rats were treated with vehicle, CA or metformin daily for 14 days by oral gavage. Fatty acid (FA) content in testis was analysed using gas chromatographyflame ionisation detection while redox indices were measured as peroxide value (PV), malondialdehyde (MDA), oxygen radical antioxidant capacity (ORAC), reduced glutathione (GSH), glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(86 reference statements)
2
3
0
Order By: Relevance
“…The increase in MDA (oxidative stress) in the diabetic testes could have been caused by both the production of ROS that accompanied the established hyperglycemia, and the decrease in antioxidant activity ( Alsenosy et al, 2019 , Sefidgar et al, 2019 ). These findings support the other studies that have reported the association between DM and oxidative stress ( Nna et al, 2019 , Oguntibeju et al, 2020 , Oyenihi et al, 2020 ). Alabi and colleagues (2020) reported the possible significance of A. difformis to extract in ameliorating oxidative stress through the Nrf2 pathway.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The increase in MDA (oxidative stress) in the diabetic testes could have been caused by both the production of ROS that accompanied the established hyperglycemia, and the decrease in antioxidant activity ( Alsenosy et al, 2019 , Sefidgar et al, 2019 ). These findings support the other studies that have reported the association between DM and oxidative stress ( Nna et al, 2019 , Oguntibeju et al, 2020 , Oyenihi et al, 2020 ). Alabi and colleagues (2020) reported the possible significance of A. difformis to extract in ameliorating oxidative stress through the Nrf2 pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of these compounds might be responsible for the biological activities demonstrated by the plant. As a result, the significant decrease in the reduction of Fe 2+ in the testes of diabetic rats compared to the control groups in this study corroborates with the report of Oyenihi et al (2020) that measured the FRAP capacity of the testes and deduced that antioxidant power was reduced when DM was induced. The antioxidant power may be compromised by oxidative stress ( Erukainure, 2019 , Pieme et al, 2017 ), further confirmed in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies showed that diabetes causes oxidative damage in rat testis. The oxidative damage in diabetic animals was confirmed by elevations in MDA level and diminishment in GSH level (21)(22)(23). Thyagaraju and Muralidhara suggested that PCO levels were higher in diabetic testis and liver tissues than non-diabetics (23).…”
Section: Discussionmentioning
confidence: 93%